TUJUAN SUPERVISI - Tri Antini; Ali Muhdi (STKIP Subang, 2026)
This study aims to describe and analyze the internal and external objectives of educational supervision, the relationship between supervision and improving educational quality, and the targets of supervision, which include teachers, learning, curriculum, and school management. The study employed a qualitative approach with library research. Data were obtained through a review of various scientific sources, including books, journals, laws and regulations, and previous research relevant to educational supervision. Data collection was conducted through documentation studies, while data analysis employed content analysis. The study results indicate that educational supervision has internal objectives, including developing teacher professionalism, improving the learning process, enhancing educator motivation, fostering school culture, and optimizing resource management. External objectives include public accountability, meeting national education standards, responding to social change, and enhancing public trust. Supervision also plays a strategic role in improving educational quality through guidance, innovation, and strengthening the implementation of educational policies. The targets of supervision, which include teachers, learning, curriculum, and school management, must be implemented in an integrated manner to achieve quality education. Therefore, educational supervision is a crucial instrument in the sustainable development of educational quality, oriented toward achieving national education goals.